Determinants of Voter Persistence in Re-elections: A Case Study of Participation Anomalies in Jambi City - Ahmad, Zakly Hanafi; Taufany, Ahmad Fahri; Amelia, Wenny Desta; Tobing, Reynlen Febrini Rezeki (JURNAL KUASA, 2026)
Re-voting (Pemungutan Suara Ulang or PSU) is a corrective mechanism in Indonesian elections often associated with voter fatigue and declining participation. However, a significant anomaly occurred at Polling Station 66 in Simpang Rimbo Village, Jambi City, during the 2024 Election, where voter turnout remained stable despite procedural repetition. This study investigates the determinants of this persistence through a qualitative case study, utilizing Expectancy-Value Theory as the analytical framework. Data were collected via in-depth interviews with voters, organizers, and community leaders. The findings reveal that high retention was driven by the strong social embeddedness of local political actors who mobilized early, serving as guarantees for voter expectancy. Furthermore, the re-voting process was successfully reframed from a mere administrative correction into a defense of local sovereignty, elevating the intrinsic value of participation. The study concludes that voter fatigue is not inevitable; it can be neutralized when there is strong political resonance between strategic actor mobilization and the collective emotional bonds of the community, challenging conventional assumptions regarding re-election dynamics.